Agentic perspective on fostering work-related learning. Issue 3 (2nd September 2017) - Vähäsantanen, Katja; Paloniemi, Susanna; Hökkä, Päivi; Eteläpelto, Anneli
ABSTRACT: Despite the increased recognition of the role that professional agency plays in work-related learning, little is known about what supports it. Based on current theoretical notions, the first purpose of this paper is to show that professional agency is closely intertwined with work-related learning. The second purpose is to introduce some main principles that promote professional agency and describe three work-related training settings that are aimed at fostering learning by taking into account agentic perspectives. These complementary settings include an identity coaching programme, a leadership coaching programme, and a work conference. Based on the qualitative meta-synthesis, the paper further provides an empirical overview of professional agency and learning in these settings. The paper contributes to the understanding of the potential of professional agency at the heart of work-related learning. To foster learning, it is necessary to create social events for the enactment and activation of agency so that social and individual resources (e.g. experiences) are utilised. Overall, the paper emphasises that individuals and communities are active crafters of their professional identities and practices, and it provides viewpoints to support their agency in work and training settings.